Reliability and validity of the Greek translation of the patient assessment of chronic illness care + (PACIC-PLUS GR) survey - Malliarou, Maria (BMC Fam Pract, 2020)
BACKGROUND: This study aimed to investigate the Patient Assessment of Chronic Illness Care+ (PACIC+) which is a tool to assess care for Chronic Conditions combining PACIC items with an overall 5As score derived from the ‘5As’ model (ask, advise, agree, assist, and arrange), and is congruent with the Chronic Care Model. In addition, the study at hand aimed to translate the PACIC+ tool into Greek and test its psychometric properties to the Greek patients. METHODS: Questionnaires were collected from 268 chronic patients. Internal consistency and reliability were determined by the calculation of Cronbach’s alpha coefficient. A confirmatory factor analysis (CFA) was conducted in order to test the construct validity of the questionnaire. Validity was further examined by investigating the correlation of PACIC+ with SF-36 and its association with sex and age. RESULTS: Internal consistency reliability was accepted with a Cronbach’s alpha above 0.70 for all PACIC+ dimensions. CFA showed that the 10-dimensional model fitted the data well (RMSEA = 0.059, CFI = 0.91 and GFI = 0.83). Most of the correlations coefficients between PACIC+ and SF-36 dimensions were significant. A significant and negative correlation was found between PACIC+ summary score, Patients’ activation and Goal Setting/ Tailoring with age. CONCLUSIONS: The Greek translation of the PACIC+ questionnaire has good psychometric properties and has proven to be a credible and valid tool to be used by Greek researchers in order to measure patients’ perceived care during treatment. It demonstrated high reliability and internal consistency, extending the applicability of this instrument to Greek speaking chronic patients.